Modelagem numérica de fluxo do aquífero cárstico-fissural do Grupo Bambuí, bacia do riacho Boi Morto no município de São Francisco, Norte de Minas Gerais - Rodrigo Sérgio de Paula (2012)
This study was carried through at the northern region of Minas Gerais State, São Francisco city and aimed at defining a numerical flow model in the fissure-karst aquifer system of Boi Morto Creek basin, middle portion of the São Francisco River basin. The expectancy is that this workcontributes with data for the planning of the local hydric resources. The geological context is related to pelite-carbonate neoproterozoic rocks of the Paraopeba subgroup, Bambuí group, and weatherd siliclastic rocks of Urucuia Group. The aquifer system studied was defined accordingto three hydrostratigraphic units: inferior fissure-karst aquifer, metapelitic aquitard and superior fissure-karst aquifer. A statistical study of the directions of fractures and ducts was conducted on outcrops selected every 1km2, annual (february 2010 to april 2011) pluviometric, fluvial andpotentiometric monitoring was done, as well as evaluation of the recharge and permeability and analysis of the conduction directions and general flow. The model was made in permanent regime using the finite differences method, through Visual Modflow 2009.1 software, considering the equivalent porous system. The model results were consistent with the previously calculated results, with absolute average error under 10%, which was considered satisfactory due to thestrong anisotropy. Regarding the precipitation (974 mm), the recharge was of 12% (118mm), the basic outflow was of 9% (89,8mm) and the superficial outflow 14 % (133 mm).